Sedentary Behaviour Patterns and Carotid Intima-Media Thickness in Spanish Healthy Adult Population - Garcia-Hermoso, A (Elsevier Ireland Ltd, 2015)
The aim of this study was to analyze the association between sedentary behaviour, as assessed by an accelerometer, and mean carotid intima-media thickness (IMT). Methods: The study included 263 healthy subjects belonging to the EVIDENT study (59.3% women). Carotid IMT was measured by carotid ultrasonography. Sedentary behaviour was measured objectively over 7 days using ActiGraph accelerometers. Thresholds of 10 consecutive minutes were used to establish sedentary bouts, and assess the number (n/day), and length ≥10min (min/day). Results: Total sedentary time and sedentary time in bouts ≥10min was higher in participants with a larger mean carotid IMT (>P75). Otherwise, this sedentary time in bouts ≥10min parameter was weakly associated with augmented carotid IMT injury in the logistic regression model. Conclusion: Total sedentary time and sedentary time in bouts ≥10min, as assessed by accelerometer, was positively but weakly associated with carotid IMT. Equally, this sedentary time in bouts ≥10min was associated with carotid injury, but disappears after adjusting for potential confounders. These findings support that reducing sedentary time and increasing breaks in bouts of sedentary time might represent a useful additional strategy in the cardiovascular disease prevention. Trial Registration: Clinical Trials.gov Identifier: NCT01083082. © 2015 Elsevier Ireland Ltd.